2017
DOI: 10.1080/03019233.2017.1288309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structure and viscosity of CaO–SiO2–MgO–30.00 wt-%Al2O3 slag by molecular dynamics simulation with FT-IR and Raman spectroscopy

Abstract: Structure of CaO-SiO 2 -MgO-30.00 wt-%Al 2 O 3 slag was investigated using molecular dynamics simulation at 1873 K, and viscosities with different basicities were measured for quantitatively studying the relationship between structure and viscosity. With the increase of basicity, the threedimensional networks formed by Si and Al are depolymerised, which is consistent with the analysis using FT-IR and Raman spectroscopy. Additionally, FT-IR analysis shows a dampening of [Al-O-Si] trough, indicating a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A Raman spectrum was also obtained, and each antifold peak in the entire Raman spectrum was fitted (fitting degree >99.9%) to further analyze the network structure. According to previous studies, [ 31,33,34 ] the characteristic peak of Al–O–Al symmetric stretching is ≈550 cm −1 , and the characteristic peaks in the range of 700–1200 cm −1 are formed by the superposition of the Al–O − or Si–O − stretching vibrations. Therein, the peak in the range of 800–820 cm −1 corresponds to Si–O–Al symmetric stretching, and the characteristic peaks in the ranges of 850–900, 900–940, 940–980, 1000–1080 cm −1 , correspond to Q Si 0 ([SiO 4 ] 4− ), Q Si 1 ([Si 2 O 7 ] 6− ), Q Si 2 ([SiO 3 ] 2− ), Q Si 3 ([Si 2 O 5 ] 2− ), respectively.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…A Raman spectrum was also obtained, and each antifold peak in the entire Raman spectrum was fitted (fitting degree >99.9%) to further analyze the network structure. According to previous studies, [ 31,33,34 ] the characteristic peak of Al–O–Al symmetric stretching is ≈550 cm −1 , and the characteristic peaks in the range of 700–1200 cm −1 are formed by the superposition of the Al–O − or Si–O − stretching vibrations. Therein, the peak in the range of 800–820 cm −1 corresponds to Si–O–Al symmetric stretching, and the characteristic peaks in the ranges of 850–900, 900–940, 940–980, 1000–1080 cm −1 , correspond to Q Si 0 ([SiO 4 ] 4− ), Q Si 1 ([Si 2 O 7 ] 6− ), Q Si 2 ([SiO 3 ] 2− ), Q Si 3 ([Si 2 O 5 ] 2− ), respectively.…”
Section: Resultsmentioning
confidence: 78%
“…It was observed that with an increase in electric field strength within 0-4 V, the broadband center of the [AlO 4 ] 5À and [SiO 4 ] 4À tetrahedral stretching peak gradually shifted toward lower wavenumbers, while the [AlO 6 ] 9À octahedral stretching peak shifted to A Raman spectrum was also obtained, and each antifold peak in the entire Raman spectrum was fitted (fitting degree >99.9%) to further analyze the network structure. According to previous studies, [31,33,34] the characteristic peak of Al-O-Al symmetric stretching is %550 cm À1 , and the characteristic peaks in the range of 700-1200 cm À1 are formed by the superposition of the Al-O À or Si-O À stretching vibrations. Therein, the peak in the range of 800-820 cm À1 corresponds to Si-O-Al symmetric stretching, and the characteristic peaks in the ranges of 850-900, 900-940, 940-980, 1000-1080 cm À1 , correspond to Q Si 0…”
Section: Effect Of DC Electric Field On Structure Of Lfsmentioning
confidence: 81%
“…Metals 2021, 11, x FOR PEER REVIEW 10 of 15 from 2 wt.% to 10 wt.% at a constant temperature, which indicates that the increase in SiO2 content becomes rate-limiting for the mass transfer at the slag-melt interface region. The reason for this phenomenon is that SiO2 increases the tendency to network formation and the degree of polymerization of the refining slag [36,37]. Furthermore, comparing the viscosity values of the designed FFS and industrial FBS at the same temperature, it is seen that when the SiO2 content is 2 wt.%, the viscosity is less than that of the industrial FBS, and increases with the SiO2 content.…”
Section: Sio2mentioning
confidence: 97%
“…P 2 O 5 is an acidic oxide with a lesser content in the molten slag [ 76 ], and it can also act as the network former in the slag, as shown in Figure 5 a [ 77 ]. The bond length of P-O is about 1.53Å [ 48 ], which is slightly shorter than the Si-O. The stability of the P-O bond is relatively weaker than the Si-O bond.…”
Section: The Evolution Of Molten Slag’s Microstructurementioning
confidence: 99%